Evaluating Optimal Parameters for Machining Selective Laser Melting Titanium Alloy Using Wire Cut Electrical Discharge Machining - Polishetty, A; Littlefair, G (IGI Global, 2020)
Titanium is known for its poor machinability characteristics due to its low thermal conductivity and high chemical reactivity. This article explores the machinability characteristics of selective laser melting (SLM) titanium alloy Ti-6Al-4V using wire cut electrical discharge machining (WEDM). For titanium alloys, exploring non-traditional machining operation such as WEDM is critical for a material failure or success in a design application. The research is to study the effect of parameters such as servo voltage, pulse on/off, and machining speed with respect to wire tension and wire feed rate on machinability. The outputs under consideration for evaluating machinability are metal removal rate (MRR) and surface finish under minimal interruption due to wire snaps. The article concludes by identifying the optimal factors responsible to produce an efficient and accurate cut with a minimum downtime.
Keywords: Machinability; Selective Laser Melting; Titanium Alloys; Wire Cut Electrical Discharge Machining